Synthesis and antimalarial activity of new 4-aminoquinolines active against drug resistant strains. Issue 107 (7th November 2016) - Kondaparla, Srinivasarao; Soni, Awakash; Manhas, Ashan; Srivastava, Kumkum; Puri, Sunil K.; Katti, S. B.
Abstract : In the present study we have synthesized a new class of 4-aminoquinoline derivatives and bioevaluated them for antimalarial activity against the P. falciparum in vitro (3D7 & K1) and P. yoelii in vivo (N-67 strain). Abstract : In the present study we have synthesized a new class of 4-aminoquinoline derivatives via replacement of the diethylamine functionality of chloroquine (CQ) with acyclic and/or cyclic amine groups containing basic tertiary terminal nitrogen and bioevaluated them for antimalarial activity against Plasmodium falciparum in vitro (CQ-sensitive strain-3D7 & CQ-resistant strain-K1) and Plasmodium yoelii in vivo (N-67 strain). Among the series, thirteen compounds showed superior antimalarial activity against K1 strain as compared to CQ. In addition, all these analogs showed 100% suppression of parasitaemia on day 4 in the in vivo mouse model against N-67 strain when administered orally. Further, biophysical studies suggest that these compounds act on the heme polymerization target.